Isolation, enrichment of a halophilic yeast Candida sp. YH and its treatability study of saline wastewater - Chí, Trần Minh; Minh, Nghiêm Ngọc (Vietnam Journal of Biotechnology, 2018)
A strain of halophilic yeast was isolated, enriched and adapted to an increasing salinity started from 5, 10 to 15 g/l NaCl to get it adapted gradually to high saline environment. Then the yeast biomass was developped in batch experiment, with each batch lasted 32 hours each, at further increased salinity to 20, 25 and 30 g/l NaCl with influent COD 5000 mg/l at pH 3.5, temperature 30oC. At salinity 20 g/l NaCl, COD removal efficiency reached over 90% from beginning and reached over 96% after 6 batches with effluent COD 203 mg/l. When the salinity increased to 25 g/l, COD removal efficiency varied within 89% to 90% in first 4 batches and reached 95% after 8 batches with effluent COD 250 mg/l. At salinity 30 g/l NaCl, COD removal efficiency decreased notably, reached less than 90% during first 5 batches and then inceased gradually, reached 93.6% only after 9 batches with effluent COD 320 mg/l. Salinity was the main factor influencing the ion equilibrium inside the yeast cells leading to decrease in substrate degradation and rate of cell. Inceased salt concentration also lead to longer adaptation time of the cells. The cell morphology of YH strain was observed by Scanning Electron Microscopy (SEM). The cells of this yeast strain has lemon-like shape, with 1.3–1.78 in width; and 2.00–2.69 µm in length. Based on the morphological characteristics and the phylogenetic analysis by alignment of ITS1-5.8S rRNA-ITS2 sequences, high homology up to 92% with Candida sp. YS W113A (AM410670)) indicated this strain as, namely, Candida sp. YH.